Centrality dependence of high-pT D meson suppression in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Busch, Oliver; Deisting, Alexander; Glässel, Peter; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; Oyama, Ken; et al. (Journal of high energy physics, 2015)
The nuclear modification factor, R AA, of the prompt charmed mesons D0, D+ and D∗+, and their antiparticles, was measured with the ALICE detector in Pb-Pb collisions at a centre-of-mass energy sNN−−−−√=2.76sNN=2.76 \sqrt{s_{N\;N}}=2.76 TeV in two transverse momentum intervals, 5 < p T < 8 GeV/c and 8 < p T < 16 GeV/c, and in six collision centrality classes. The R AA shows a maximum suppression of a factor of 5-6 in the 10% most central collisions. The suppression and its centrality dependence are compatible within uncertainties with those of charged pions. A comparison with the R AA of non-prompt J/ψ from B meson decays, measured by the CMS Collaboration, hints at a larger suppression of D mesons in the most central collisions. Open image in new window